IoT on Door Security Control Prototypes based RFID and Bluetooth - Sri Mulyati; Sumardi Sadi (Universitas Muhammadiyah Tangerang, 2019)
Door security system wherever needed, because to protect the parts that are stored, whether in housing, warehousing, offices, or in the industrial world. Security system currently developing digitally based is by using the Internet of Things (IoT) system. Microcontrollers, HC05 Bluetooth modules and RFID modules based IoT make it possible to be a door guard. The current problem is that even though the door is locked, it still occurs theft, and assume that the cost of making security is too expensive. Solution to the problem it is making RFID and Bluetooth-based door security control prototypes with the IoT system. The purpose of this study is to make a prototype of door security control devices based RFID and Bluetooth with an IoT system. For access to the door using an ID card and Smartphone. The method used is laboratory experiments. This research produces a prototypes of door security control devices versatile based IoT RFID and Bluetooth, at a cost cheap, economical, and effective to use. Keywords: Arduino, HC05, RFID, Servo Motor, LCD